Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s10533-020-00644-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of sediment controls of nitrogen cycling in an agricultural stream

Abstract: Agricultural streams receive large inputs of nutrients, such as nitrate (NO3−) and ammonium (NH4+), which impact water quality and stream health. Streambed sediments are hotspots of biogeochemical reactivity, characterised by high rates of nutrient attenuation and denitrification. High concentrations of nitrous oxide (N2O) previously observed in stream sediments point to incomplete denitrification, with sediments acting as a potentially significant source of global N2O. We investigated the effect of sediment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…For example, Webster et al (2003) reported a mean gross NO − 3 -N uptake rate of 111 mg m −2 day −1 (range: 0-7299 mg m −2 day −1 ) across 11 headwater streams in N. America, while in a metaanalysis of instream nutrient retention, Ensign and Doyle (2006) reported a mean NO − 3 -N uptake rate of 170 mg m −2 day −1 across 29 s-order streams. The general pattern we observed of increasing NO − 3 -N uptake from spring to autumn is consistent with other studies (Jarvie et al, 2018;Reisinger et al, 2019) and was also identified by Comer-Warner et al (2020) in isotope study of the sediments of Wood Brook. Hence, we suggest heterotrophic denitrification may have become an increasingly dominant pathway for removal during autumn in our shaded study system.…”
Section: Temporal Dynamics Of Net Nutrient Uptakesupporting
confidence: 92%
“…For example, Webster et al (2003) reported a mean gross NO − 3 -N uptake rate of 111 mg m −2 day −1 (range: 0-7299 mg m −2 day −1 ) across 11 headwater streams in N. America, while in a metaanalysis of instream nutrient retention, Ensign and Doyle (2006) reported a mean NO − 3 -N uptake rate of 170 mg m −2 day −1 across 29 s-order streams. The general pattern we observed of increasing NO − 3 -N uptake from spring to autumn is consistent with other studies (Jarvie et al, 2018;Reisinger et al, 2019) and was also identified by Comer-Warner et al (2020) in isotope study of the sediments of Wood Brook. Hence, we suggest heterotrophic denitrification may have become an increasingly dominant pathway for removal during autumn in our shaded study system.…”
Section: Temporal Dynamics Of Net Nutrient Uptakesupporting
confidence: 92%
“…The sediment consists of complex aggregates of microorganisms, including bacteria, archaea, algae, fungi, protozoa, and metazoans, which play a vital role in the primary production and biogeochemical cycle of freshwater ecosystems [21,22]. Microorganisms in lake sediments play an irreplaceable role in the carbon cycle [23,24], nitrogen cycle [25,26], and biodegradation [27]. For example, there is a thin layer in the sediments (from several millimeters to several centimeters), in which anaerobic processes dominate, with the participation of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…An ISCO peristaltic pump (Lincoln, NE, USA) passes 1 L of stream water through these sensors every hour. Stream monitoring is supplemented with campaign‐based sampling facilitated by networks of surface water ISCO autosamplers, for instance during tracer tests (Blaen, Brekenfeld, et al, 2017; Blaen, Khamis, et al, 2017), as well as spatially nested multi‐level mini‐piezometers installed in the streambed to investigate streambed biogeochemical processes and groundwater–surface water interactions (Comer‐Warner et al, 2019; Comer‐Warner et al, 2020). A stage‐discharge relationship for the Wood Brook was developed by Blaen, Khamis, et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…An ISCO peristaltic pump (Lincoln, NE, USA) passes 1 L of stream water through these sensors every hour. Stream monitoring is supplemented with campaign-based sampling facilitated by networks of surface water ISCO autosamplers, for instance during tracer tests(Blaen, Brekenfeld, et al, 2017;Blaen, Khamis, et al, 2017), as well as spatially nested multi-level minipiezometers installed in the streambed to investigate streambed biogeochemical processes and groundwater-surface water interactions(Comer-Warner et al, 2019;Comer-Warner et al, 2020). A stagedischarge relationship for the Wood Brook was developed byBlaen, Khamis, et al (2017).Volumetric soil moisture content in the main BIFoR FACE facility is monitored by 12 cm long frequency domain reflectometry sensors(CS655 by Campbell Scientific [Logan, USA], ±3% v/vfor typical soils) installed diagonally from the surface in triangular groups of three spaced 1 m apart, with two groups in the 'control' and 'treatment' patches and one group in the undisturbed patches, and monitoring at 15 to 30 min resolution.…”
mentioning
confidence: 99%